2019
DOI: 10.1136/bmjopen-2019-032310
|View full text |Cite
|
Sign up to set email alerts
|

Applying a whole systems lens to the general practice crisis: cross-sectional survey looking at usage of community pharmacy services in England by patients with long-term respiratory conditions

Abstract: ObjectiveUK policy initiatives aiming to extend community pharmacy services to moderate patient demands and to reduce general practitioners’ (GPs) workload have had limited success. This study used marketing theory to identify factors that could influence patients to make better use of community pharmacies within the primary care pathway.DesignCross-sectional postal survey design applying the ‘7Ps marketing mix’ (‘product’, ‘price’, ‘place’, ‘promotion’, ‘people’, ‘process’ and ‘physical evidence’).SettingGrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…However, patient and public attitudes were influenced by frequency of service usage and the perceived impact or benefit from using these services, which is what we observed in our study. A recent cross-sectional survey looking at usage of community pharmacy services in England by patients with long-term respiratory conditions further reiterates our findings: most patients in the survey preferred to use GP practices for diagnostic services, but preference was associated with services previously accessed at the pharmacy [24]. Both studies identified professionalism of the whole pharmacy team and timeliness of consultations as features that enhance patient and public use of pharmacy services, in addition to convenience and ease of access, which were also identified by patients in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, patient and public attitudes were influenced by frequency of service usage and the perceived impact or benefit from using these services, which is what we observed in our study. A recent cross-sectional survey looking at usage of community pharmacy services in England by patients with long-term respiratory conditions further reiterates our findings: most patients in the survey preferred to use GP practices for diagnostic services, but preference was associated with services previously accessed at the pharmacy [24]. Both studies identified professionalism of the whole pharmacy team and timeliness of consultations as features that enhance patient and public use of pharmacy services, in addition to convenience and ease of access, which were also identified by patients in our study.…”
Section: Discussionsupporting
confidence: 78%
“…Despite patients overall being broadly positive for pharmacists providing extended services, awareness is low [4,[24][25]. Increased collaboration between GPs and pharmacists has been identified as key to successful implementation and integration of new pharmacy services, with studies reporting these services not always perceived as beneficial or useful from the GPs' point of view [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent crosssectional survey looking at usage of community pharmacy services in England by patients with long-term respiratory conditions further reiterates our findings: most patients in the survey preferred to use GP practices for diagnostic services, but preference was associated with services previously accessed at the pharmacy. 24 Both studies identified professionalism of the whole pharmacy team and timeliness of consultations as features that enhance patient and public use of pharmacy services, in addition to convenience and ease of access, which were also identified by patients in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Despite patients overall being broadly positive for pharmacists providing extended services, awareness is low. 4,[24][25] Increased collaboration between GPs and pharmacists has been identified as key to successful implementation and integration of new pharmacy services, with studies reporting these services not always perceived as beneficial or useful from the GPs' point of view. [26][27] This study was part of a larger evaluation of the STTT service and findings need to be interpreted within this context.…”
Section: Discussionmentioning
confidence: 99%
“…45 In order to maximise community pharmacists' contribution to the health service and potential to alleviate GP workload, a whole system-level approach will be required. 46 As the pharmacy profession responds to COVID-19, innovative and extended methods of practice will be needed. For example, in order to promote social distancing and facilitate self-isolation while ensuring that patients continue to have access to vital pharmacy services, new methods of service delivery will play an increasing role.…”
Section: Other Areasmentioning
confidence: 99%